Bapineuzumab for mild to moderate Alzheimer's disease in two global, randomized, phase 3 trials. Issue 1 (December 2016) - Vandenberghe, Rik; Rinne, Juha; Boada, Mercè; Katayama, Sadao; Scheltens, Philip; Vellas, Bruno; Tuchman, Michael; Gass, Achim; Fiebach, Jochen; Hill, Derek; Lobello, Kasia; Li, David; et al.
Abstract Background Our objective was to evaluate the efficacy (clinical and biomarker) and safety of intravenous bapineuzumab in patients with mild to moderate Alzheimer's disease (AD). Methods Two of four phase 3, multicenter, randomized, double-blind, placebo-controlled, 18-month trials were conducted globally: one in apolipoprotein E ε4 carriers and another in noncarriers. Patients received bapineuzumab 0.5 mg/kg (both trials) or 1.0 mg/kg (noncarrier trial) or placebo every 13 weeks. Coprimary endpoints were change from baseline to week 78 on the 11-item Alzheimer's Disease Assessment Scale–Cognitive subscale and the Disability Assessment for Dementia. Results A total of 683 and 329 patients completed the current carrier and noncarrier trials, respectively, which were terminated prematurely owing to lack of efficacy in the two other phase 3 trials of bapineuzumab in AD. The current trials showed no significant difference between bapineuzumab and placebo for the coprimary endpoints and no effect of bapineuzumab on amyloid load or cerebrospinal fluid phosphorylated tau. (Both measures were stable over time in the placebo group.) Amyloid-related imaging abnormalities with edema or effusion were confirmed as the most notable adverse event. Conclusions These phase 3 global trials confirmed lack of efficacy of bapineuzumab at tested doses on clinical endpoints in patients with mild to moderate AD. Some differences in the biomarker results were seen compared with the other phase 3 bapineuzumab trials. No unexpected adverse events were observed. Trial registration Noncarriers (3000) ClinicalTrials.gov identifierNCT00667810 ; registered 24 Apr 2008. Carriers (3001) ClinicalTrials.gov identifierNCT00676143 ; registered 2 May 2008.